Changes in Maxillary Canine Pulpal Blood Flow During Dentoalveolar Distraction Osteogenesis. - Ersahan, Seyda; Sabuncuoglu, Fidan Alakus (My University, 2016)
The aim of this study was to assess the effects of dentoalveolar distraction osteogenesis (DD) on the pulpal blood flow (PBF) of maxillary canines.

A laser Doppler flowmeter (LDF) was used to measure PBF in maxillary canines of 10 patients undergoing DD (study group) and 10 nonsurgical subjects who received no orthodontic treatment (control group). PBF was measured at baseline, at 4 and 7 days postoperatively, at the end of distraction and at the end of consolidation in the study group and at similar time-points in nonsurgical control subjects. Data were analyzed using paired and Student t tests, with the significance level set at 0.05.

Study findings showed that baseline PBF values did not differ significantly between groups. PBF in the control group did not vary over time; however, in the study group, an initial decrease in PBF was observed at 4 days postoperatively and was followed by a gradual increase to preoperative levels at the end of distraction.

During the DD latency period, there appears to be a short-lived ischemic phase when perfusion of pulp tissue declines; however, blood-flow returns to normal by the end of distraction.